SHARP: a distributed GPU‐based ptychographic solver. Issue 4 (14th July 2016) - Marchesini, Stefano; Krishnan, Hari; Daurer, Benedikt J.; Shapiro, David A.; Perciano, Talita; Sethian, James A.; Maia, Filipe R. N. C.
Abstract : The SHARP framework provides fast images from high‐throughput ptychographic datasets and a corner stone for demanding higher‐dimensional analysis such as spectro‐ptychography or tomo‐ptychography. Abstract : Ever brighter light sources, fast parallel detectors and advances in phase retrieval methods have made ptychography a practical and popular imaging technique. Compared to previous techniques, ptychography provides superior robustness and resolution at the expense of more advanced and time‐consuming data analysis. By taking advantage of massively parallel architectures, high‐throughput processing can expedite this analysis and provide microscopists with immediate feedback. These advances allow real‐time imaging at wavelength‐limited resolution, coupled with a large field of view. This article describes a set of algorithmic and computational methodologies used at the Advanced Light Source and US Department of Energy light sources. These are packaged as a CUDA‐based software environment named SHARP (http://camera.lbl.gov/sharp ), aimed at providing state‐of‐the‐art high‐throughput ptychography reconstructions for the coming era of diffraction‐limited light sources.